A Tandem Prins/Friedel‐Crafts Cyclization Strategy for the Stereoselective Synthesis of Hexahydro‐2H‐benzo[g]chromenes. Issue 38 (13th October 2022) - Meng, Shuyu; Guo, Wentao; Liu, Jie; Zheng, Jie; Wang, Quanrui
Abstract: A tandem Prins/Friedel‐Crafts cascade strategy has been developed for the synthesis of hexahydro‐2 H ‐benzo[ g ]chromene derivatives. Under action of equimolecular amount of BF3 etherate, δ, ϵ‐unsaturated alcohols and arylacetaldehydes are coupled to form oxocarbenium ion intermediates, which are captured by the alkene moiety through a favored six‐membered transition state. The Prins‐cyclization resultant tertiary carbenium ions undergo consecutive intra molecular Friedel–Crafts cyclization to create the tricyclic products. This process enables a tandem formation of three new chemical bonds in one single operation with high yields and stereoselectivity in most cases. When cyclic substituents are involved, a variety of spiro derivatives could also be synthesized successfully, which further proved the robustness of this methodology. Abstract : A novel strategy has been developed for the one‐pot stereoselective synthesis of hexahydro‐2 H ‐benzo[ g ]chromenes from δ, ϵ‐unsaturated alcohols and arylacetaldehydes using 100 mol % BF3 etherate. The reaction proceeds through a tandem Prins/Friedel‐Crafts cascade involving oxocarbenium ion and tertiary or benzylium ion intermediates. The use of market purchasable starting precursors and operation simplicity make this protocol attractive and feasible.